PENERAPAN MEDIA GAMBAR DALAM MENINGKATKAN KEMAMPUAN BERBICARA ANAK KELOMPOK B2 DI TK HARAPAN PULAU GADANG KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR TAHUN 2021 - Gusniati (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
The early age of a child's life which is very decisive in the development of his intelligence is at the age of 0-8 years or what is often referred to as the Golden Age. At this time the child will develop very critically and quickly absorb whatever the child gets from his environment. Each individual early childhood always has its own characteristics or uniqueness, it is the characteristics and uniqueness of early childhood that distinguishes each child with the age above him, so that his education is also considered to need to be special. Based on the background of the problem, the formulation of the problem in this study is whether the application of image media in improving the speaking ability of children in group B2 in Harapan Kindergarten, Pulau Gadang? The purpose of this research is to improve speaking skills through pictures in the children of group B2 in Harapan Kindergarten, Gadang Island. The research method in this study refers to the classroom action research model, in class action research the procedures carried out include three cycles and methods of collecting the data used is the method of observation and documentation. very well developed (BSB) as many as 1 child (4.7%) then in the second cycle of action the results obtained were 6 children (28.5%) who developed very well (BSB) and the third cycle achieved the results of 15 children ( 71.4%) who developed very well (BSB).